Identities, Cultures, Spaces : Dialogue and Change. - Kuhn, Fernando (Cambridge Scholars Publishing, 2013)
The intense circulation of people, contents and goods that characterises the current process of globalisation has led to unprecedented cultural encounters, which can be perceived either as the source of conflicts or opportunities for dialogue. This volume adopts a multidisciplinary approach to address issues that emerge at the confluence of ""identity"" and ""culture""; and in their articulation, with the involvement of distinct geographic factors, by means of analyses of the notions and discours ...